Design of a task delegation system in a context of standardized projects - Chávez Cobián, Alfredo Leonardo (2022)
The task delegation, in the organizational context, is a process by which the responsibility of carrying out a task is assigned to a suitable person. However, in various companies, this process is carried out subjectively and manually, leaving aside the performance of the worker. This situation affects the effectiveness of the company's operation and produces dissatisfaction among the workers. In this article, based on a company in the telecommunications sector that operates under standardized projects, a scheme and a computer tool are established for the task delegation based on the performance of the worker. For this, a systematic mapping study was carried out in order to identify and characterize the existing solutions on delegation systems based on performance. Then, once the scope of the solution was delimited, the development of the “Delegator” computer tool and the validation of the delegation of tasks based on performance proceeded. From a practical perspective, the established assignment scheme allows a categorization based on the criteria: task start date, task deadline, number of inputs and number of skills required; and the tool facilitates its application to the defined case of the company. From a theoretical perspective, the categorization of workers using the SVM is performed according to four variables of the task to be delegated, two of them are new variables that count the required characteristics of the worker and the entries of the task.